Novel measures to assess work-life balance: A systematic review of last 5 years (2018-2023) - Amelia RIZZO; Murat YILDIRIM; Maria Grazia MAGGIO; Hicham KHABBACHE; Juan GOMEZ-SALGADO; Mahmood BAHRAMIZADEH; Driss AIT ALI; Lukasz SZARPAK; Pietro CRESCENZO; Giada IUELE; Nicola BRAGAZZI; Livio TARCHI; et al. (Journal of Health and Social Sciences)
Introduction: In the contemporary, fast-paced, and demanding world of work, achieving an effective Work- Life Balance (WLB) has become paramount. This study aimed to conduct a brief overview of measurement tools developed over the last five years (2018-2023) to assess work-life balance. Methods: The selection of studies was conducted in accordance with the Joanna Briggs Institute (JBI) Critical Appraisal Tool and PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, ensuring the inclusion of high-quality research. Results: A total of 1,816 records were screened. After the application of inclusion and exclusion criteria, eight studies of 512 were deemed suitable for the current review. All newly developed tools focused on overcoming the limitations of previous instruments, and how to best capture the multidimensional nature of WLB. These novel assessments also offer a theoretical contribution on how to best operatize WLB in the clinical or research setting. Discussion: This review provides a valuable resource by providing an up-to-date overview of measures developed in the last five years to evaluate WLB. It underscores the continued importance of this topic in contemporary society and the ongoing efforts to enhance our understanding of it. It also highlights the need for further research to refine and develop standardized cultural and contextual variations measures. Such measures are essential for fostering a better understanding of WLB in today's diverse and ever-evolving work environments. This review underlines the significance of WLB in the modern world and the importance of continuing research efforts to keep pace with the evolving nature of work.